Tracking the impacts of El Niño drought and fire in human-modified Amazonian forests - Berenguer, Erika; Lennox, Gareth D.; Ferreira, Joice; Malhi, Yadvinder; Aragão, Luiz E.O.C.; Barreto, Julia Rodrigues; Del Bon Espírito-Santo, Fernando; Figueiredo, Axa Emanuelle S.; França, Filipe; Gardner, Toby Alan; Joly, Carlos A.; Palmeira, Alessandro F.; et al. (Proceedings of the National Academy of Sciences, 2021)
With humanity facing an unprecedented climate crisis, the conservation of tropical forests has never been so important – their vast terrestrial carbon stocks can be turned into emissions by climatic and human disturbances. However, the duration of these effects is poorly understood, and it is unclear whether impacts are amplified in forests with a history of previous human disturbance. Here, we focus on the Amazonian epicenter of the 2015–16 El Niño, a region that encompasses 1.2% of the Brazilian Amazon. We quantify, at high temporal resolution, the impacts of an extreme El Niño (EN) drought and extensive forest fires on plant mortality and carbon loss in undisturbed and human-modified forests. Mortality remained higher than pre-El Niño levels for 36 mo in EN-drought–affected forests and for 30 mo in EN-fire–affected forests. In EN-fire–affected forests, human disturbance significantly increased plant mortality. Our investigation of the ecological and physiological predictors of tree mortality showed that trees with lower wood density, bark thickness and leaf nitrogen content, as well as those that experienced greater fire intensity, were more vulnerable. Across the region, the 2015–16 El Niño led to the death of an estimated 2.5 ± 0.3 billion stems, resulting in emissions of 495 ± 94 Tg CO2. Three years after the El Niño, plant growth and recruitment had offset only 37% of emissions. Our results show that limiting forest disturbance will not only help maintain carbon stocks, but will also maximize the resistance of Amazonian forests if fires do occur.*
Keywords: Amazon; Degradation; El Niño; Forest fires; Logging